Worthwhile theological dialogue of the abrahamic faiths: opportunities and challenges - Hashi, Abdurezak Abdulahi (2014)
Judaism, Christianity and Islam are among universal religious faiths, which had influenced humanity over thousands of years. Like other universal religious faiths, religious traditions of Abrahamic faiths are widely practiced by many societies in different corners of the world. In addition, these religious faiths have exhibited closely interrelated traditions and historical connections. Thus, given the presence of these religious communities in the affairs of the contemporary global societies, one might argue that peace and mutual understanding among the communities of Abrahamic faiths, presumably, contributes significantly to the global peace and stability. However, despite the fact that these three religions share vital historical and traditional connections with each other, there are cases in which the relationship of the followers of these three religions is marked by tensions and sometime hostile encounters. In this regard, one of the fundamental questions is, if indeed, these three religions share, as they do, common vital grounds, what is the source of given tensions among the adherents of these faiths? This question can be answered in different ways, however this paper argues that given tensions among the adherents of these faiths, are due to misunderstanding and lack of worthwhile religious dialogue on given religious beliefs. This paper uses analytical method, and addresses opportunities and challenges of worthwhile theological dialogue of Abrahamic faiths.